2015
DOI: 10.1016/j.ebiom.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood, Rather Than Venous Blood, is a Better Source for Circulating Melanoma Cells

Abstract: BackgroundCTCs provide prognostic information and their application is under investigation in multiple tumor types. Of the multiple variables inherent in any such process, none is more important to outcome than the appropriateness of the sample source. To address this question, we investigated CTCs in paired peripheral venous and arterial blood specimens obtained from stage IV uveal melanoma patients.MethodsBlood specimens were obtained from both common femoral arteries and antecubital veins in 17 uveal melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 33 publications
(38 reference statements)
2
42
0
1
Order By: Relevance
“…A strong positive correlation has been reported between the number of CTCs, the stage of disease, and overall patient survival (Mumford & Robertson, ). However, the melanoma CTC field remains burdened by inconsistencies and discrepancies in approaches to detect CTCs, which limits the clinical utility of CTCs for diagnostic, prognostic, and therapeutic efficacy assessments (Salvianti et al., ; Terai et al., ). Circulating tumor cells have been detected in stage I/II melanoma patients (Khoja et al., ) suggesting that solitary seed cells or circulating microemboli may rest or be trapped at secondary organ sites during any stages of melanoma development.…”
Section: Introductionmentioning
confidence: 99%
“…A strong positive correlation has been reported between the number of CTCs, the stage of disease, and overall patient survival (Mumford & Robertson, ). However, the melanoma CTC field remains burdened by inconsistencies and discrepancies in approaches to detect CTCs, which limits the clinical utility of CTCs for diagnostic, prognostic, and therapeutic efficacy assessments (Salvianti et al., ; Terai et al., ). Circulating tumor cells have been detected in stage I/II melanoma patients (Khoja et al., ) suggesting that solitary seed cells or circulating microemboli may rest or be trapped at secondary organ sites during any stages of melanoma development.…”
Section: Introductionmentioning
confidence: 99%
“…Terrai et al konnten mit diesem Verfahren ZMZs mittels Antikörpern, gerichtet gegen das melanomassoziierte Antigen (HMW-MAA), in einer hohen Frequenz (100 %) und Anzahl (Median 5, Schwankungsbreite: 1-168) aus arteriellen Blutproben, verglichen zu venösen Proben (52,9 %, Median: 1, Schwankungsbreite: 0-8), bei Patienten mit multiplen systemischen Metastasen nachweisen [21]. Dieses Verfahren setzt einerseits voraus, dass die disseminierten Melanomzellen den epithelialen Marker exprimieren, andererseits der Marker nicht von anderen zirkulierenden Zellen exprimiert wird.…”
Section: Nachweismethoden Zirkulierender Melanomzellen (Zmz) Bei Chorunclassified
“…This scenario would be consistent with a high ability of CTCs to spread to distant sites and adhere to endothelial cells in capillary beds before reaching the periphery, possibly leading to the establishment of new Editorial metastases. Previous studies have indeed reported that arterial blood contains more CTCs compared to the venous circulation in patients [9], suggesting that alternative phlebotomy locations might reveal unforeseen CTC patterns and allow CTC isolation before their entrapment within distant sites. Lastly, in the metastatic setting, it is also unclear whether growing metastases in different organs are characterized by different CTC shedding capabilities.…”
Section: Fluctuating Numbers Of Circulating Tumor Cells In Cancer Patmentioning
confidence: 96%